2023
DOI: 10.3390/jpm13050725
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine in Oral Health and Diseases: A Systematic Review

Abstract: Precision medicine (PM) is personalized medicine that can develop targeted medical therapies for the individual patient, in which “omics” sciences lead to an integration of data that leads to highly predictive models of the functioning of the individual biological system. They enable rapid diagnosis, assessment of disease dynamics, identification of targeted treatment protocols, and reduction of costs and psychological stress. “Precision dentistry” (DP) is one promising application that need further investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…This paradigm shift from a one-size-fits-all approach to a patient-centric model holds immense promise in optimizing treatment outcomes and minimizing adverse effects in oral cancer patients. Furthermore, the ongoing advancements in high-throughput sequencing technologies and computational algorithms continue to propel the field forward, fostering a deeper understanding of the molecular complexities of oral cancer and paving the way for innovative targeted therapies and precision oncology interventions [ 5 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paradigm shift from a one-size-fits-all approach to a patient-centric model holds immense promise in optimizing treatment outcomes and minimizing adverse effects in oral cancer patients. Furthermore, the ongoing advancements in high-throughput sequencing technologies and computational algorithms continue to propel the field forward, fostering a deeper understanding of the molecular complexities of oral cancer and paving the way for innovative targeted therapies and precision oncology interventions [ 5 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of pain frequently does not correlate with the nature or degree of tissue injury [ 3 ]. The perception of pain is individual and is a multifaceted phenomenon that encompasses psychological and emotional processes along with nociceptive and non-nociceptive impulses in ascending pathways [ 4 , 5 , 6 ]. These pathways are, in turn, connected to the activation of descending pain-inhibitory systems [ 2 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Germ-free mice, raised in sterile conditions without exposure to microorganisms, have been used as experimental models to study the impact of germ-free mice on bone density and structure. Microbiota transplantation studies have shown that introducing a diverse and healthy microbiota positively affects bone health in recipients, while transplanting from diseased or imbalanced donors may lead to compromised bone density and structure [20][21][22][23][24]. In human trials, probiotics have been found to modulate the GM, with certain strains associated with increased calcium absorption and improved bone density.…”
Section: Experimental Evidence Of the Impact Of The Gastrointestinal ...mentioning
confidence: 99%
“…For now, there have not been detailed instructions formulated that would vouch for successful living tissue replacement with no adverse effects. This narrative review provides the reader with up-to-date information and novel trends in the field of regenerative dentistry and tissue replacement therapy [9][10][11][12], including the most current utilization, applications, improvements, and methods over the last five years (2019-August 2023). To replace living tissue in the human body using biocompatible 3D-printed grafts (usually in the form of scaffolds), we need to understand numerous biological processes and interactions between native tissues, cells, and scaffolds, promote their migration towards the injured area, ensure adequate vascularization and biodegradation, etc.…”
Section: Introduction 1historical Background and Significance Of Scaf...mentioning
confidence: 99%